2018
DOI: 10.22216/jbe.v3i2.3493
|View full text |Cite
|
Sign up to set email alerts
|

Profitabilitas Dan Kebijakan Dividen Terhadap Nilai Perusahaan

Abstract: <p><em>The purpose of this study is to examine the affect of profitability and dividend policy toward the firm’s value on the bank companies which are listed in Indonesia Stock Exchange.The number of populations are all banks companies which are listed in Indonesia Stock Exchange.</em><em> </em><em>The sample was selected using purposive sampling method, and obtained sample of 30 companies.</em><em> Data source is the annual report of banking companies taken thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0
31

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 0 publications
3
9
0
31
Order By: Relevance
“…Semakin tinggi Return on Equity (ROE) maka semakin bagus karena perolehan laba yang dihasilkan oleh perusahaan tersebut akan semakin besar, begitupun sebaliknya semakin rendah Return on Equity (ROE) suatu perusahaan atau Return on Equity (ROE) mengarah pada angka negatif maka perusahaan tersebut akan mengalami kerugian. Hasil penelitian ini mendukung Lubis et al (2017), Martha et al (2018), dan Fadillah et al (2019 menemukan bahwa profitabilitas berpengaruh terhadap nilai perusahaan.…”
Section: Pengaruh Profitabilitas Terhadap Nilai Perusahaanunclassified
See 1 more Smart Citation
“…Semakin tinggi Return on Equity (ROE) maka semakin bagus karena perolehan laba yang dihasilkan oleh perusahaan tersebut akan semakin besar, begitupun sebaliknya semakin rendah Return on Equity (ROE) suatu perusahaan atau Return on Equity (ROE) mengarah pada angka negatif maka perusahaan tersebut akan mengalami kerugian. Hasil penelitian ini mendukung Lubis et al (2017), Martha et al (2018), dan Fadillah et al (2019 menemukan bahwa profitabilitas berpengaruh terhadap nilai perusahaan.…”
Section: Pengaruh Profitabilitas Terhadap Nilai Perusahaanunclassified
“…Profitabilitas penting dalam perusahaan karena dapat menginformasikan jumlah keuntungan yang di dapat dari hasil penjualan dan juga menunjukan apakah perusahaan tersebut mempunyai prospek yang baik di masa yang akan datang karena semakin tinggi tingkat profitabilitas maka kelangsungan hidup perusahaan tersebut akan lebih terjamin. Hasil penelitian Lubis et al (2017), Martha et al (2018), dan Fadillah et al (2019) menemukan bahwa profitabilitas berpengaruh terhadap nilai perusahaan.…”
unclassified
“…This is in contrast to Anita & Yulianto (2016), who found that dividend policy has no effect on firm value. Research that has been conducted by Martha et al (2018) still has its limitations. Increasing the number of companies and using sectors other than banking, such as infrastructure, utilities and transportation as research objects.…”
Section: Introductionmentioning
confidence: 99%
“…Then the dividend policy is proxied by the dividend payout ratio and the firm value is proxied by the price to book value. Furthermore, Martha et al (2018) suggest increasing the number of samples and using companies in the infrastructure, utilities and transportation sectors as research objects.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the main goal of the company is to make a profit. However, despite this objective, companies that have gone public have the objective of increasing the value of their companies, which is reflected in the market price of their shares (Martha, 2018). The value of the company is the investor's perception of the level of success of the company associated with stock prices and corporate profitability (Salempang, 2016) High organization esteem mirrors that investor thriving is additionally high, so the high estimation of the organization can demonstrate that the organization can expand the success of investors.…”
Section: Introductionmentioning
confidence: 99%